Pitcairnia queroana (Pitcairnioideae, Bromeliaceae), a striking new species from Chiapas state, Mexico - Espejo, Adolfo; López-Ferrari, Ana Rosa (Phytotaxa, 2015)
Pitcairnia queroana, known only from the state of Chiapas, Mexico, is here described and illustrated. The new taxon superficially resembles P. sulphurea but differs from it by the presence of long petioles, longer inflorescence with more than 60 flowers, purple calyx, and the conspicuous and dense white-lanate-tomentose indument that covers all the inflorescence. An identification key for the taxa of the genus present in this state is also included.